SYSTEM MODEL OF IMPLEMENTATION OF THE PRINCIPLE OF FAILURE RESISTANCE OF HIGH-DEGREE AND AVERAGE AVAILABILITY ON THE LIFE CYCLE - Vorobiev , V. M.; Zakharchenko , V. A.; Enchev , S. V.; Berezovsky, B. N.; Kondratenko, S. V. (Problems of Informatization and Management, 2005)
The article forms a system model for the implementation of the principle of avionics fault tolerance of a high degree of integrity and readiness on the basis of the "target tree". The goals and objectives of the design and implementation of avionics on the basis of IMA are considered.